The impact of possible migration scenarios after "Brexit" on the state pension system - Angus Armstrong; Justin van de Ven (Economies, 2016)
The purpose of this paper is to explore the impacts of changes in migration flows-in particular, those resulting from possible migration policy changes after a UK exit ('Brexit') from the European Union (EU)-on the finances of the UK state pension system. We find that the aggregate effects of considered shocks to immigration associated with Brexit on the funding of UK state pensions are dwarfed by associated uncertainties, and by coincident cost increases due to population aging and (domestic) pension's policy.
Keywords: F22; J61; H55; 330; migration; Brexit; state pension; fiscal effects